1993
DOI: 10.1016/0014-5793(93)81678-s
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ability of minor groove binders to induce supercoiling in DNA

Abstract: The effect of various non-intercalating minor groove binders on closed circular DNA in the presence of topoisomerase I has been studied by means of agarose gel electrophoresis. Analogues of the netropsin series (lexitropsins) and SN-6999 can effectively produce positive supercoils, as indicated by analysis of the topoisomers in the presence of chloroquine and the evaluated linking number changes. Analogues of the distamycin series are less effective, and bisquaternary ammonium heterocycles, as well as DAPI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…1, inset) at the concentrations used. In addition, the agreement between values for DNA in intact cells and values for solubilized DNA from these cells suggests that minimal error was attributable to changes in medium chemistry, packing effects, or binding hindrance by supercoiling (61). Thus, under restricted staining time, concentration, and temperature conditions used, DAPI appears to be a specific stain for the DNA of small nonpigmented bacterium-like organisms when it is used with a size parameter such as forward light scatter.…”
Section: Downloaded Frommentioning
confidence: 90%
See 1 more Smart Citation
“…1, inset) at the concentrations used. In addition, the agreement between values for DNA in intact cells and values for solubilized DNA from these cells suggests that minimal error was attributable to changes in medium chemistry, packing effects, or binding hindrance by supercoiling (61). Thus, under restricted staining time, concentration, and temperature conditions used, DAPI appears to be a specific stain for the DNA of small nonpigmented bacterium-like organisms when it is used with a size parameter such as forward light scatter.…”
Section: Downloaded Frommentioning
confidence: 90%
“…Stains such as PicoGreen (62), Hoechst 33258, SYBR Green (4,38), SYTOX Green (66), Syto 13 (18), YOYO, YO-PRO (39), and TOTO (24) have also been used, but the specificity and species dependence of these stains have not been evaluated. Among these stains the in vitro binding of DAPI by DNA is best understood (61). DAPI is bright and stable enough and is minimally affected by DNA conformation (1).…”
mentioning
confidence: 99%
“…So, the compounds probably accumulate on DNA without binding it. Störl et al reported that 6 well-known DNA minor groove-binding agents could change the Lk number like the intercalators did, but in a different way (Störl et al, 1993). The ability of BM3 and BM4 to change the Lk number depends on how many of them bind per 1 base pair of DNA.…”
Section: Human Topoisomerase Iia Inhibition Mechanisms Of Bm3mentioning
confidence: 99%
“…This situation could be explained as these compounds could accumulate on DNA minor grooves and they could give different results depending on their concentrations. It was reported that the agents without intercalation properties could still bind on DNA minor grooves to inhibit enzymes that manipulate DNA (Störl et al, 1993;Reddy et al, 1999;Racane et al, 2010). For example, it was shown that the agents that induce structural changes on DNA were active on topo I and II catalysis and DNAprotein interactions in vitro (Bailly et al, 1999).…”
Section: Human Topoisomerase Iia Inhibition Mechanisms Of Bm3mentioning
confidence: 99%
“…The catalytic reaction requires a high-energy cofactor and occurs by ATP hydrolysis. Members of these, clinically relevant, drugs are defined by their ability to interrupt the breaking/reunion reaction of DNA topoisomerase I by trapping reversible topoisomerase I cleavable complexes (Storl et al, 1993;Megan et al, 1993;Chen et al, 1993). The possibility of monitoring variations in DNA supercoiling, mediated by small organic molecules, is of considerable interest for obtaining information about the determinants of topological changes involved in DNA structural transitions, affecting transcriptional regulatory activity.…”
mentioning
confidence: 99%